Inhibition of RXRA-mediated PLA2G2A improves delirium in COPD mice by regulating endoplasmic reticulum stress pathway and inhibiting cell apoptosis: Role of RXRA and PLA2G2A in COPD - Zhang, Teng; Wang, Guodong (Cellular and Molecular Biology, 2024)
Delirium is a common psychiatric complication of chronic obstructive pulmonary disease (COPD). The relief of delirium is considered one of the beneficial ways to treat COPD. However, there are currently no specific drugs that alleviate delirium in COPD patients. Our research aimed to elucidate the specific mechanisms underlying delirium in COPD mice, while also seeking more effective therapeutic targets. In our study, bioinformatics analysis and qRT PCR were used to identify key factors in the development of delirium in COPD animal models. Open field and elevated plus maze tests were used to detect delirium in mice. Tunel staining and HE staining were used to analyze the apoptosis of mouse hippocampus cells. EdU and CCK-8 experiments were used to analyze PC-12 cells vitality and proliferation. JASPAR online database, dual luciferase reporting experiments, ChIP experiments, and IF staining were used to analyze the interaction between RXRA and PLA2G2A. RXRA is highly expressed in the brain tissue of COPD mice with delirium symptoms. The downregulation of RXRA inhibits the delirium state in COPD mice. This is mainly due to the reduction of endoplasmic reticulum stress and cell apoptosis by inhibiting the expression of RXRA. In addition, we also confirmed that RXRA is a transcription factor of PLA2G2A. RXRA has an inhibitory effect on the expression of PLA2G2A. In vitro experiments have confirmed that inhibition of the RXRA/PLA2G2A axis reduces cell apoptosis, thereby alleviating the occurrence and development of delirium in COPD mice. Inhibition of the RXRA/PLA2G2A axis reduces endoplasmic reticulum stress and cell apoptosis. This process alleviates the development of delirium in COPD mice.